A snicker of magic - Lloyd, Natalie (Scholastic Inc., 2015)
Felicity Pickle is not like other people--where other people collect baseball cards or whatever, Felicity collects words. Words people say, think, and want. The word she wants, in all of her family's moving around, is "home." Finally, her mother's van called the "Pickled Jalapeno" rolls into Midnight Gulch, where she hopes maybe she has found the word "home," and maybe even "friend."